Three new species and two new records of Utricularia L. (Lentibulariaceae) from Northern Thailand - Suksathan, Piyakaset; Parnell, John A.N. (Thai Forest Bulletin (Botany), 2014)
Additional occurrences of Utricularia L. in Thailand are documented. Three new species, U. inthanonensis Suksathan & J. Parn., U. phusoidaoensis Suksathan & J. Parn. and U. spinomarginata Suksathan & J. Parn. are described and illustrated. Utricularia babui Yadav, Sardesai & Gaikwad and U. furcellata Oliver are reported as new records and an extension for the range of U. garrettii P. Taylor is documented.